2020
DOI: 10.1093/conphys/coaa078
|View full text |Cite
|
Sign up to set email alerts
|

Urethral catheterization as an alternative method for collecting sperm in the black-footed ferret (Mustela nigripes)

Abstract: The endangered black-footed ferret (BFF; Mustela nigripes) is an important example of the benefits of assisted reproduction in species conservation with both semen evaluation and artificial insemination using fresh and frozen sperm being successfully incorporated into the breeding program. Currently, electroejaculation (EE) is routinely utilized for semen collection in BFFs, a technique that requires custom equipment and experienced operators, and does not consistently yield viable samples in this species. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…UC is generally preferred by practitioners, as it is less invasive than EEJ, quicker to perform, and does not require the expensive and specific equipment needed for EEJ [ 28 , 29 ]. The successful use of UC may be dependent upon the use of medetomidine, an alpha-2-adrenergic agonist, within the anesthesia protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UC is generally preferred by practitioners, as it is less invasive than EEJ, quicker to perform, and does not require the expensive and specific equipment needed for EEJ [ 28 , 29 ]. The successful use of UC may be dependent upon the use of medetomidine, an alpha-2-adrenergic agonist, within the anesthesia protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-adrenoreceptor agonists have been shown to stimulate contractions of the vasa deferentia in rats [ 30 ], which, in turn, may facilitate the movement of semen into the urethra. Only one male (#16) in this summary was anesthetized without the use of medetomidine, and therefore, it is difficult to conclude whether medetomidine use is strictly necessary when conducting UC for polar bears, but it is commonly used when conducting UC in other species [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The challenge now is to apply more quantitative sperm functional approaches to improve testing of sperm cryopreservation protocols and the insemination of functionally high-quality sperm for the artificial propagation of those cat species that are on the endangered species list. Mackie et al [ 42 ] experimented successfully using UC in the BFF and showed that it was not only less invasive than EE but that semen of good quality could be retrieved.…”
Section: Mammalia (Mammals)mentioning
confidence: 99%